Analisa SWOT Untuk Mendukung Kinerja UMKM AS&B Di Surabaya - Tri Wahjoedi; Kusuma Adi Rahardjo; Agung Dwi Nugroho; Sofyan Lazuardi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This community service text aims to present improvement strategies using SWOT analysis carried out to provide support to AS&B MSME companies in Surabaya in facing the challenges of increasing competition in the food industry. This SWOT approach involves identifying internal factors, namely strengths and weaknesses, and external factors, namely opportunities and threats. From this analysis, recommendations for action to improve operational performance were produced, 2 SO strategies, 2 WO strategies, 2 ST strategies and 3 WT strategies. To increase sales, AS&B MSMEs should increase product variety and quality, use social media for marketing, provide empathetic service, and carry out attractive promotions. This combination of strategies is expected to significantly increase the company's performance and sales. It provides systematic and adaptive guidance to improve a company's competitiveness in a dynamic business environment.